Southeastern Asia fall armyworms are closely related to populations in Africa and India, consistent with common origin and recent migration - Nagoshi, Rodney N. (Sci Rep, 2020)
The discovery of fall armyworm, a native of the Western Hemisphere, in western Africa in 2016 was rapidly followed by detections throughout sub-Saharan Africa, India, and most recently southeastern Asia. This moth pest has a broad host range that threatens such important crops as corn, rice, millet, and sorghum, creating concern for its potential impact on agriculture in the Eastern Hemisphere. Although genetic data suggest populations sampled in Africa and India originate from a recent common source, it is not known whether this is the case for populations in southeastern Asia, nor whether the subgroup with a preference for rice and millet is present in the region. This study found through comparisons of genetic markers that the fall armyworm from Myanmar and southern China are closely related to those from Africa and India, suggesting a common origin for these geographically distant populations. The results are consistent with a single recent introduction into the Eastern Hemisphere followed by rapid dispersion. The molecular similarities include discrepancies between the genetic markers that brings into question whether the subpopulation most likely to be a threat to rice and millet is present in significant numbers in Asia.